Assessment of lethal electrocardiography knowledge levels of non-physician healthcare personnel - Mustafa Polat; Ali Karakus; Bircan Kara; Veysel Karani Belen (Al Ameen Journal of Medical Sciences)
Aim: This study aimed to determine the extent to which non-physician healthcare personnel recognize life-threatening rhythms in Electrocardiography (ECG), and to identify the importance of professional experience or in-service training in recognizing life-threatening rhythms. Material and Methods: This descriptive study was designed to measure the ECG knowledge levels of healthcare personnel. It was completed with a total of 532 non-physician healthcare personnel including Paramedics, Emergency Medical Technicians (EMTs), nurses working in intensive care units, and inpatient clinics in Hatay province, Turkey. An 18-question survey form was used as the data collection tool in the research. Seven of the questions were related to participants' age, workplace, duration of employment, in-service training, etc., while eleven were related to ECG rhythms. Results: A total of 532 healthcare workers participated in the study, with the majority falling in the age range of 20-25 years (41.9%).Nurses comprised the largest group among the participants (37.4%). The majority of participants (75%) had been employed for 8 years or more, yet 66.9% had not attended any ECG courses during their employment, and 34% had received formal ECG training as part of their undergraduate or in-service education for five years or more. Among the units where participants worked, it was observed that 49.9% of the respondents were emergency department workers, where ECG applications were very frequent. Conclusion: According to the findings of the study, nurses were the group that answered the most questions, and the most frequently answered question incorrectly was about AF and ANT MI. It is suggested that ECG courses be added as compulsory subjects to the nursing and paramedic-EMT training curriculum, accompanied by laboratory and simulation practices.